Ketamine Rescues Hippocampal Reelin Expression and Synaptic Markers in the Repeated-Corticosterone Chronic Stress Paradigm - Johnston, Jenessa N.; Thacker, Jonathan S.; Desjardins, Charissa; Kulyk, Brian D.; Romay-Tallon, Raquel; Kalynchuk, Lisa E.; Caruncho, Hector J. (Frontiers in Pharmacology, 2020)
In order to evaluate some possible mechanisms underlying the fast- antidepressant actions of ketamine we used the repeated corticosterone paradigm to assess the effects of ketamine on reelin-positive cells, as well as the effects of both reelin and ketamine on hippocampal and cerebellar synaptosomes, and on serotonin transporter clustering in peripheral lymphocytes. Our data shows that ketamine rescues the deficits in reelin-positive cells in the hippocampal subgranular zone induced by repeated corticosterone. Reelin and ketamine similarly rescue synaptic expression of mTOR and p-mTOR that were decreased by corticosterone. Reelin, but not ketamine, was able to rescue patterns of serotonin transporter clustering in the periphery. These findings display ketamine as a powerful modulator of reelin expression and lend strength to further evaluation of the putative fast antidepressant-like actions of reelin.